Assume y varies inversely as x, how do you write the equation given y=-6 when x=-3?

2 Answers
May 29, 2017

#yprop(1/x)#

so, #y = k/x#

With x = -3 and y = -6 we have:

#-6 = k/-3#

=> k = 18

Then, #y = 18/x#

or, #xy = 18#

:)>

May 29, 2017

Answer:

#y = 18/x#

Explanation:

This sounds like inverse proportionality.

The standard writing for such a formula is: #y = k/x#

Given the information, y = -6 when x =-3, we can find the constant "k".
#-6 = k/-3 iff k = -6*(-3)=18#

Now we know "k", we write the formula that sitifies y = -6 when x = -3 as #y = 18/x#